2020
DOI: 10.1007/s10911-020-09443-6
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Transcription Factor CREB3L4 Contributes to the Progression of Human Breast Carcinoma

Abstract: Breast carcinoma(BC)is the most common cancer type among females globally. Understanding the molecular pathways that trigger the development of BC is crucial for both prevention and treatment. As such, the role of transcription factors (TFs) in the development of BC is a focal point in this field. CREB3s play a critical role in initiating the unfolded protein response (UPR); however, the role of CREB3 family members in breast cancer development remains largely unknown. Here, we mined the ONCOMINE database for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We used DAKO En-Vision (K5007) for immunohistochemical analysis, and two pathologists from Southwest Hospital independently completed the pathological assessment of each patient's tissue specimen. The final score of the immune response = the percentage of stained area × the intensity of staining, the staining area score method: 75-100% = 4, 50-74% = 3, 25-49% = 2; staining intensity score: high staining = 3, moderate staining =2, weak staining=1, negative=0, the final score range of staining is 0-12 ( 42 ). Follow-up information of patients was collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used DAKO En-Vision (K5007) for immunohistochemical analysis, and two pathologists from Southwest Hospital independently completed the pathological assessment of each patient's tissue specimen. The final score of the immune response = the percentage of stained area × the intensity of staining, the staining area score method: 75-100% = 4, 50-74% = 3, 25-49% = 2; staining intensity score: high staining = 3, moderate staining =2, weak staining=1, negative=0, the final score range of staining is 0-12 ( 42 ). Follow-up information of patients was collected.…”
Section: Methodsmentioning
confidence: 99%
“…The 160 research subjects were divided into three groups according to their ages, young people (≤39), middle-aged people (35,41,(43)(44)(45)(46)(47)(48)(49)(50), and old people (≥50). The results of Fisher's exact test showed that there were 14 young people High expression of nanog occurred in 9 persons (64.3%), 17 out of 50 subjects of middle-aged people had high expression of nanog (34%), and 29 out of 96 subjects of elderly had high expression of nanog (30.2 %) The difference between the above three groups is statistically significant (c2=5.941, P=0.047).…”
Section: Nanog Correlates With Bclc Stages and Tumor Growth In Pretreated Hcc Patientsmentioning
confidence: 99%
“…However, protein abundance of CREB3L1, which belongs to the same TF subfamily as CREB3L4, is predictive of the response of triple negative breast cancer to doxorubicin-based therapy [71]. In a recent paper, Pu et al already identified that expression of CREB4L3 is increased in most breast cancer types, and that the downregulation leads to a decreasing proliferation, induces cell cycle arrest and apoptosis [72]. We observed a CREB3L4 binding site in a genomically modified REM associated to CCDC137.…”
Section: Discussionmentioning
confidence: 56%
“…CREB3L4 (cyclic amplification responsive element binding protein 3-like 4) is part of the CREB/ATF family of transcriptional factors, and it is primarily expressed in the prostate gland in humans as well as prostate and breast cancer cell lines[ 22 ]. CREB3L4 has been shown (by immunostaining) to have a higher expression level in cancerous prostate cells than in adjacent noncancerous cells[ 22 ] and it has also been shown to contribute to the progression of breast cancer[ 23 ]. INTS3 (integrator complex subunit 3) is part of the Integrator complex which is associated with the C-terminal domain of RNA polymerase II[ 24 ].…”
Section: Amplification Of Chromosome 1q Genesmentioning
confidence: 99%